A Comparative Review of Material Properties for Current and Future Dental Filling Nanomaterials (International Journal of Engineering Materials and Manufacture, 2021)
ABSTRACTNanomaterials observe specialized properties relative to gross materials. Due to their small size, specialized nanomaterial properties include decreased reactivity, an increased surface area to volume ratio, heightened structural properties, and in some cases, antimicrobial and antibacterial effects. Current researchers are looking to use nanoparticle/nanomaterial properties to solve prevalent dental issues that cannot be addressed with traditionally used materials. This paper will serve as an extensive review of current nanomaterial applications as they pertain to dental fillings and dental filling processes. Comparative assessments of traditional materials used in dental fillings will be made as well as comparative assessments of currently used nanomaterials in dental fillings. Material comparisons are based on criteria pertaining to biocompatibility, toxicity, reactivity, cost, and antimicrobial/antibacterial properties. When comparing the three most currently used dental filling nanomaterials – Carbon-Based Nanotubes, Silica Nanoparticles and Silver-Coated Nanoparticles – it was observed that Silica Nanoparticles demonstrated the greatest material advantage and should be recommended for continued use. Issues regarding future developmental dental filling applications of graphene nanoparticles, organic nanoparticles and gold nanoparticles will also be discussed.Keywords: Nanomaterials, antibacterial, dental fillings, silica resins, biocompatibility.